The Missiological Spirit : Christian Mission Theology in the Third Millennium Global Context - Yong, Amos (Cambridge : James Clarke & Co., 2015)
The field of the theology of mission has developed variously across Christian traditions in the last century. Pentecostal scholars and missiologists have made their share of contributions to this area. 'The Missiological Spirit' brings the insights of Pentecostal theologian Amos Yong to the discussion. It delineates the major features of what will be argued as central to a viable vision and praxis for Christian mission in a postmodern, post-Christendom, post-Enlightenment, post-Western, and postcolonial world. What emerges will be a distinctively pentecostally and evangelically informed missio.
Part III. North American Missiology: Theology of Mission Post-ChristendomChapter 7: The Missiology of Jamestown 1607-2007 and Beyond: Toward a Postcolonial Theology of Mission in North America; Theological Questions after Jamestown; Missiological Prospects after Jamestown; Toward a Postcolonial Theology of Mission in North America; Chapter 8: The Buddhist-Christian Encounter in the USA: Reflections on Christian Practices; The Buddhist-Christian Encounter in America: A Brief Overview; Toward a Christian Theology of Interreligious Practices in Dialogue with Buddhism
Includes bibliographical references.
Vendor-supplied metadata.
Master record variable field(s) change: 072
Keywords: Missions -- Theory; RELIGION / Christian Ministry / Missions; Missions; RELIGION / Christian Ministry / Missions; Theology, Doctrinal; Missions -- Theory; Electronic books